Fatigue and cognitive impairment in Post-COVID-19 Syndrome: A systematic review and meta-analysis - Ceban, Felicia; Ling, Susan; Lui, Leanna M.W.; Lee, Yena; Gill, Hartej; Teopiz, Kayla M.; Rodrigues, Nelson B.; Subramaniapillai, Mehala; Di Vincenzo, Joshua D.; Cao, Bing; Lin, Kangguang; Mansur, Rodrigo B.; et al. (Brain, behavior, and immunity, 2022)
•Fatigue and cognitive impairment are amongst the most common and debilitating symptoms of post-COVID-19 syndrome.•Approximately 1 in 3 individuals experienced fatigue 12 or more weeks following COVID-19 diagnosis.•Approximately 1 in 5 individuals exhibited cognitive impairment 12 or more weeks following COVID-19 diagnosis.•There was an elevation in proinflammatory markers and functional impairment in a subset of post-COVID individuals. COVID-19 is associated with clinically significant symptoms despite resolution of the acute infection (i.e., post-COVID-19 syndrome). Fatigue and cognitive impairment are amongst the most common and debilitating symptoms of post-COVID-19 syndrome. To quantify the proportion of individuals experiencing fatigue and cognitive impairment 12 or more weeks following COVID-19 diagnosis, and to characterize the inflammatory correlates and functional consequences of post-COVID-19 syndrome. Systematic searches were conducted without language restrictions from database inception to June 8, 2021 on PubMed/MEDLINE, The Cochrane Library, PsycInfo, Embase, Web of Science, Google/Google Scholar, and select reference lists. Primary research articles which evaluated individuals at least 12 weeks after confirmed COVID-19 diagnosis and specifically reported on fatigue, cognitive impairment, inflammatory parameters, and/or functional outcomes were selected. Two reviewers independently extracted published summary data and assessed methodological quality and risk of bias. A meta-analysis of proportions was conducted to pool Freeman-Tukey double arcsine transformed proportions using the random-effects restricted maximum-likelihood model. The co-primary outcomes were the proportions of individuals reporting fatigue and cognitive impairment, respectively, 12 or more weeks following COVID-19 infection. The secondary outcomes were inflammatory correlates and functional consequences associated with post-COVID-19 syndrome. The literature search yielded 10,979 studies, and 81 studies were selected for inclusion. The fatigue meta-analysis comprised 68 studies, the cognitive impairment meta-analysis comprised 43 studies, and 48 studies were included in the narrative synthesis. Meta-analysis revealed that the proportion of individuals experiencing fatigue 12 or more weeks following COVID-19 diagnosis was 0.32 (95% CI, 0.27, 0.37; p < 0.001; n = 25,268; I2 = 99.1%). The proportion of individuals exhibiting cognitive impairment was 0.22 (95% CI, 0.17, 0.28; p < 0.001; n = 13,232; I2 = 98.0). Moreover, narrative synthesis revealed elevations in proinflammatory markers and considerable functional impairment in a subset of individuals. A significant proportion of individuals experience persistent fatigue and/or cognitive impairment following resolution of acute COVID-19. The frequency and debilitating nature of the foregoing symptoms provides the impetus to characterize the underlying neurobiological substrates and how to best treat these phenomena. PROSPERO (CRD42021256965).